Sistem Pakar Diagnosa Penyakit Pada Ibu Hamil Menggunakan Metode Forward Chaining - Jenie Sundari; Siti Wulandari; Yusnia Budiarti; Esron Rikardo Nainggolan (LPPM STIKI MALANG, 2023)
Pregnant women can be attacked by pregnancy disease, the disease can be known from the symptoms it causes, however, to find out exactly what disease is suffered by pregnant women, an expert or obstetrician is needed. In this study a website-based expert system was designed using basic rules with the forward chaining inference method aimed at helping pregnant women in diagnosing pregnancy diseases early on. This expert system is capable of diagnosing diseases suffered by pregnant women in accordance with the symptom questions posed to be answered by pregnant women, will display the results of the diagnosis, details about the disease and how the disease is treated.